Consumer Loss Aversion and the Intensity of Competition - Heiko Karle; Martin Peitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Consider a differentiated product market in which all consumers are fully informed about match value and price at the time they make their purchasing decision. Initially, consumers become informed about the prices of all products in the market but do not know the match values. Some consumers have reference-dependent utilities'i.e., they form a reference-point distribution with respect to match value and price that will make them realize gains or losses if their eventually chosen product performs better or, respectively, worse than their reference point in both dimensions. Loss aversion in the match-value dimension leads to a less competitive outcome, while loss aversion in the price dimension leads to a more competitive equilibrium than a market in which consumers are not subject to reference dependence. Depending on the weights consumers attach to the price and the match-value dimension, a market with loss-averse consumers may be more or less competitive than a market with consumers that do not have reference-dependent utilities. We also show that consumer loss aversion tends to lead to higher prices if the market accommodates a larger number of ?rms.
urn:nbn:de:bvb:19-epub-13235-5
Keywords: 330; Loss Aversion; Reference-Dependent Utility; Behavioral Industrial Organization; Imperfect Competition; Product Differentiation; Unvollkommener Wettbewerb; Produktdifferenzierung; Wettbewerb; Konsumentenverhalten; Prospect Theory; Theorie